Glorification of Misogyny and Violence in Pakistani Tv Dramas and its Impact on Young Women in Karachi - Zulfiqar, Fatima; Hafeez, Erum; Aziz, Atif (Pakistan Journal of Humanities and Social Sciences, 2023)
Pakistani TV dramas package and glorify misogynistic behavior as gestures of romance. It systematically portrays man-handling, eve-teasing, stalking, assault as normalized behaviors necessary to control women. Stereotypical tropes are reinforced regarding both genders, sustaining the status quo between them. Such content when aired on national television distorts the notion of consent, self-expression, freedom, and right to dignity in the minds of the audience. This research aims to explore how Pakistani TV dramas have portrayed violence against women under the guise of romantic myths over the past fifteen years and how this narrative when displayed to the audience contributes to the normalcy of abuse against women. The study aspires to provide insights that can benefit women in Karachi to understand how various storylines incorporated in dramas glorify violence under the pretext of romance, honor, and tradition. The research consists of both qualitative and quantitative analysis, in which 250 women were included in the survey and seven industry experts were interviewed.